Distinguishing Colored Links - Roth, Grant (My University, 2014)
A colored link is a link where all of the components are colored. The purpose of this study was to determine whether changing the color changes the link, and how much information is gained by changing the colors of the components.
Color poster with text and diagrams.
Keywords: Links; Mathematics; Posters